Pengaruh Audit Tenure Dan Audit Fee Terhadap Kualitas Audit - Regina Putri Heryana; Harry Z. Soeratin (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the influence of audit tenure and audit fee on audit quality in the context of audit practices in Indonesia. Using a qualitative approach with library research methods, this study examines various academic and professional literature published between 2014-2024. The results show that audit tenure has a non-linear effect on audit quality, with optimal quality achieved in the middle period (4-6 years) of engagement. Audit fees are found to have a positive relationship with audit quality, albeit with important limitations regarding auditor independence. The interaction between these variables shows a complex pattern, where the optimal combination varies based on industry characteristics and client business complexity. This research contributes significantly to the development of audit regulations and practices in Indonesia, particularly in the context of digital transformation and increasing business complexity. Practical implications include recommendations for developing more flexible regulatory frameworks, improving audit quality control systems, and developing auditor competencies in the use of audit technology.